ANALISIS PENGARUH INTENSITAS BERMAIN GAME ONLINE TERHADAP MOTIVASI DAN PRESTASI BELAJAR SISWA KELAS X TJKT DI SMK NEGERI 1 KUPANG - Devidson Dillak, Edgar; Magdalena Beatrice Sogen, Maria; Yanni Ariswati Fallo, Diana (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to analyze the effect of online game playing intensity on the learning motivation and academic achievement of Grade X TJKT students at SMK Negeri 1 Kupang. The rapid growth of digital technology has increased students' engagement with online games, which may influence their learning behavior and academic performance. This study employed a quantitative approach using a correlational survey design. The research sample consisted of 30 students selected through proportionate stratified random sampling. Data were collected through observation, interviews, questionnaires, achievement tests, and documentation. The collected data were analyzed using descriptive statistics, normality tests, linearity tests, simple linear regression, and General Linear Model (GLM) Multivariate analysis with the assistance of SPSS version 24.0. The findings revealed that the intensity of online game playing among students was categorized as high, while both learning motivation and academic achievement were categorized as low. The results of the simple linear regression analysis indicated that online game playing intensity had a significant effect on both learning motivation and academic achievement. Furthermore, the GLM Multivariate analysis demonstrated that online game playing intensity simultaneously affected students' learning motivation and academic achievement. These findings suggest that excessive online game playing has a negative influence on students' academic outcomes. Therefore, proper time management and supervision from teachers and parents are essential to help students balance recreational activities and academic responsibilities, thereby improving learning motivation and academic achievement.